Refining duration and frequency thresholds of restless legs syndrome diagnosis criteria - Ohayon, Maurice M; Bagai, Kanika; Roberts, Laura W; Walters, Arthur S; Milesi, Cristina (Neurology, 2016)
This study assesses the prevalence of restless legs syndrome (RLS) using DSM-5 criteria and determines what is the most appropriate threshold for the frequency and duration of RLS symptoms. The Sleep-EVAL knowledge base system queried the interviewed subjects on life, sleeping habits, and health. Questions on sleep and mental and organic disorders (DSM-5, ICD-10) were also asked. A representative sample of 19,136 noninstitutionalized individuals older than 18 years living in the United States was interviewed through a cross-sectional telephone survey. The participation rate was 83.2%. The prevalence of the 4 leg symptoms describing RLS occurring at least 1 d/wk varied between 5.7% and 12.3%. When the frequency was set to at least 3 d/wk, the prevalence dropped and varied between 1.8% and 4.5% for the 4 leg symptoms. Higher frequency of leg symptoms was associated with greater distress and impairment with a marked increase at 3 d/wk. Symptoms were mostly chronic, lasting for more than 3 months in about 97% of the cases. The prevalence of RLS according to DSM-5 was 1.6% (95% confidence interval 1.4%-1.8%) when frequency was set at 3 d/wk. Stricter criteria for frequency of restless legs symptoms resulted in a reduction of prevalence of the disorder. The prevalence was further reduced when clinical impact was taken into consideration. In order to avoid inflation of case rates and to identify patients in whom treatment is truly warranted, using a more conservative threshold of 3 times or greater per week appears the most appropriate.